Attitudes toward deprescribing among older adults with dementia in the United States. Issue 6 (10th March 2022) - Growdon, Matthew E.; Espejo, Edie; Jing, Bocheng; Boscardin, W. John; Zullo, Andrew R.; Yaffe, Kristine; Boockvar, Kenneth S.; Steinman, Michael A.
Abstract: Background: People with dementia (PWD) take medications that may be unnecessary or harmful. This problem can be addressed through deprescribing, but it is unclear if PWD would be willing to engage in deprescribing with their providers. Our goal was to investigate attitudes toward deprescribing among PWD. Methods: This was a cross‐sectional study of 422 PWD aged ≥65 years who completed the medications attitudes module of the National Health and Aging Trends Study (NHATS) in 2016. Proxies provided responses when a participant was unable to respond due to health or cognitive problems. Attitudinal outcomes comprised responses to two statements from the patients' attitudes toward deprescribing questionnaire and its revised version (representing belief about the necessity of one's medications and willingness to deprescribe); another elicited the maximum number of pills that a respondent would be comfortable taking. Results: The weighted sample represented over 1.8 million PWD; 39% were 75 to 84 years old and 38% were 85 years or older, 60% were female, and 55% reported six or more regular medications. Proxies provided responses for 26% of PWD. Overall, 22% believed that they may be taking one or more medicines that they no longer needed, 87% were willing to stop one or more of their medications, and 50% were uncomfortable taking five or more medications. Attitudinal outcomes were similar across sociodemographic and clinical factors. PWD taking ≥6 medications were more likely to endorse a belief that at least one medication was no longer necessary compared to those taking <6 (adjusted probability 29% [95% confidence interval (CI), 22%–38%] vs. 13% [95% CI, 8%–20%]; p  = 0.004); the same applied for willingness to deprescribe (92% [95% CI, 87%–95%] vs. 83% [95% CI, 76%–89%]; p  = 0.04). Conclusions: A majority of PWD are willing to deprescribe, representing an opportunity to improve quality of life for this vulnerable population.